Mudharabah Savings Scheme for Business Blessings in Increasing Customer Loyalty of KCP Bank Mega Syariah Cipto Cirebon - Indri Nurliani; Gama Pratama; Mohammad Ridwan (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to find out the Mudharabah Scheme of Business Blessing Savings in Increasing Customer Loyalty of KCP Bank Mega Syariah Cipto Cirebon The method used is a qualitative method that is descriptive, where the method includes direct research in the field by collecting data through observation to the KCP Bank Mega Syariah Cipro Cirebon then interviewing the resource persons, namely Bank employees and customers who use the Business Blessing Savings Account. And conducting documentation to the relevant part to complete the information in this study. The results of this study stated that the Mudharabah contract scheme for Business Blessing Savings at Bank Mega Syariah KCP Cipto Cirebon has an important role in increasing customer loyalty. The implementation of the Mudharabah contract scheme and maintaining communication with customers brings a number of benefits to customers, such as flexibility in fund management and fair distribution of profits. Bank Mega Syariah KCP Cipto Cirebon is responsible for the investment capital invested by Tabungan Berkah Bisnis customers in accordance with the previously agreed proportions.